(untitled) (The University of Nairobi Journal of Language and Linguistics, 2023)
This paper is a brief description and illustration of all that a single verb form can contain in Lubukusu as an agglutinating Bantu language (of Kenya). From left to right, the most complex verb form will have the following ten morphemes: preroot negation marker, subject marker, tense marker, object marker, root, applicative marker, aspect marker, mood marker, aspect emphasizer1, and postroot negation marker. Here is an example, in its orthographic form: se-ba-khamu-lom-el-eng-e-kho-ta ‘they will not be speaking for him repeatedly’, in which the root is lom ‘speak’. Since negation in Lubukusu is double-marked, the English not is represented by two separate morphemes, se- and -ta. The paper describes each one of the ten morphemes above, with the lion’s share of space being accorded to the categories of tense and aspect, as these are divided into many sub-categories: past, present, and future tenses, on the one hand, and progressive, habitual, perfective, sequential, and iterative aspects, on the other hand.